Help-Seeking Behaviour among Youth Drug Abusers in Kuching, Sarawak - Joan Sim, Jo Jo; Kamsiah, Ali (Agensi Antidadah Kebangsaan, 2021)
Statistics show that youth in Malaysia have been recorded a significant number among the drugs abusers. Past studies find that youth who are facing drugs abuse problem do not seek professional help or do not even seek help. Thus, the study aims to explore the pattern and experience of youth drug abusers during help-seeking. Methodologically, the study employs qualitative approach to have in-depth understanding about the help-seeking behaviour and pattern of the youth drug abusers before their admission to rehabilitation clinic. The study is carried out in a drugs rehabilitation clinic in Kuching area targeting the youths who are currently undergoing voluntary inpatient treatment in the clinic. The sampling is identified using purposive technique. Instruments used for the study includes indepth interview by using guided interview questions. The findings are analysed using content analysis to develop themes through the verbatim data. Findings show that majority of the participants never had the intention to seek help until the family members took action. The admission helps some of the youth to start having the intention in seeking help, improving the relationship with family members and having some positive changes on themselves. The findings of the study have implications on the community with the drug abusing youth in prevention and recovery policy.